Effective Expression of the Serratia marcescens Phospholipase A1 Gene in Escherichia coli BL21(DE3), Enzyme Characterization, and Crude Rapeseed Oil Degumming via a Free Enzyme Approach - Yang, Peizhou; Wu, Yun; Jiang, Suwei; Zheng, Zhi; Hou, Zhigang; Mu, Dongdong; Xiao, Wei; Jiang, Shaotong; Yang, Yung-Hun (Frontiers in Bioengineering and Biotechnology, 2019)
Crude oil degumming by phospholipid removal is crucial to guarantee oil quality. Phospholipase degumming could produce green vegetable oil by reducing energy consumption and protecting the environment. To develop a novel phospholipase for oil degumming, we cloned the Serratia marcescens outer membrane phospholipase A gene (OM-PLA1) and expressed its 33 KDa protein in engineered Escherichia coli BL21(DE3). OM-PLA1 activity reached 18.9 U mL−1 with the induction of 0.6 mM isopropyl β-D-1-thiogalactopyranoside for 4 h. The optimum temperature and pH were 50 °C and 7.5, respectively. Mg2+, Ca2+, Co2+, and Mn2+ at 0.1 mM L−1 significantly increased OM-PLA1 activity. The kinetic equations of OM-PLA1 and Lecitase Ultra were y=13.7x+0.74 (Km=18.53 mM, Vmax=1.35 mM min−1) and y=24.42x+0.58 (Km=42.1 mM, Vmax=1.72 mM min−1), respectively. The phosphorus content decreased from 22.6 mg kg−1 to 9.3 mg kg−1 with the addition of 15 units of free recombinant OM-PLA1 into 150 g of crude rapeseed oil. OM-PLA1 has the close degumming efficiency with Lecitase Ultra. The S. marcescens outer membrane phospholipase gene (OM-PLA1) possessed higher substrate affinity and catalytic efficiency than Lecitase Ultra. This study provides an alternative approach to achieve crude vegetable oil degumming with enzymatic technology.